989. Role of Bone Biopsy and Deep Tissue Culture for Antibiotic Stewardship in Diabetic Foot Infections. (15th December 2022) - Hockney, Sara M; Steker, Danielle; Krueger, Karen M; Bhasin, Ajay; Williams, Janna L; Galvin, Shannon
Abstract: Background: Bone biopsy is the gold standard for identifying the etiology of infectious osteomyelitis (OM) but is not always done in the setting of diabetic foot infections (DFIs), even in settings where resistant organisms are common. This study aimed to describe organisms most frequently identified on bone biopsy or deep tissue culture and determine how culture data impacted antibiotic management in patients with DFIs. Methods: We retrospectively reviewed all patients admitted with a DFI between 2018 and 2020 and selected for patients diagnosed with infectious OM of the lower extremity for whom bone biopsy or deep tissue culture was obtained. Statistics were performed in R version 4.2.0. Results: Of 305 patients with DFI, 47 patients received 41 deep tissue cultures and 29 bone biopsies for a total of 70 cultures. Of 45 (64%) positive cultures, 36 (80%) had gram positive organisms and 24 (34%) had gram negative organisms. Multidrug resistant organisms were isolated in 7 (14.9%) patients, including 5 cases of MRSA (10.2%) and 2 cases of ESBL-producing organisms (4.3%). Pseudomonas aeruginosa was isolated in 3 (6.4%) patients. Culture data resulted in antibiotic changes in 41 (87.2%) patients. Therapy was narrowed in 29 (61.7%) patients and broadened due to inadequate empiric coverage in 4 patients (8.5%). Culture-directed therapy was started in 4 (8.5%) patients in which it had initially been withheld. Culture data from 18 (40%) patients showed sensitivity to an oral treatment regimen with high bioavailability. There was no significant difference in rates of antibiotic utilization at discharge between patients who underwent bone biopsy or deep tissue culture relative to those who did not (80% vs 75%, p=0.857). There was a trend towards utilization of less MRSA coverage (38.2% vs 50.5%, p=0.16) and Pseudomonas coverage (34.0% vs 41.9%, p=0.36) in patients undergoing bone biopsy or deep tissue culture, but this did not reach statistical significance. Table 1: Bacteria isolated from deep tissue culture or bone biopsy and effect on antibiotic therapy Figure 1: Empiric antibiotics in hospital vs culture directed antibiotics on discharge Conclusion: In patients with DFIs, deep tissue and bone biopsy cultures were infrequently obtained but resulted in targeted therapy changes in most patients. While culture data usually allowed for narrowing of antibiotics, it revealed inadequate empiric coverage in a subset of patients. Disclosures: Janna L. Williams, MD, Abbvie: COVID19 Infection Prevention Consultant Shannon Galvin, MD, Gilead: Grant/Research Support.